Pelestarian Budaya Natoni (Tutur Adat) pada Atoin Meto (Timor Dawan): Studi Tentang Sinergi Antara Pemerintah dan Masyarakat di Desa Oefafi Kecamatan Kupang Timur Kabupaten Kupang - Velti Iriani Tabuna; Esrah D. N. A. Benu; Diana S. A. Natalia Tabun (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2026)
Natoni culture is an oral tradition of the Atoin Meto community that embodies significant social, cultural, and local identity values for the Timorese people. However, modernization, changing lifestyles, and the declining interest of younger generations have contributed to the weakening practice and regeneration of this cultural tradition. This study aims to analyze the forms of synergy between the government and the community in preserving Natoni culture in Oefafi Village, East Kupang District, Kupang Regency. The research employed a qualitative approach, using interviews, observations, and documentation to collect data from village government officials, traditional leaders, community figures, youth representatives, and cultural practitioners. The analysis was guided by Antonio Gramsci’s theory of hegemony, focusing on the dimensions of consensus and leadership. The findings reveal that natoni remains actively practiced in various traditional and social events as a medium for transmitting values, cultural identity, and respect for ancestral traditions. The synergy between the government and the community is reflected through village policies, budgetary support, cultural training programs, the involvement of traditional institutions, and active community participation in sustaining the tradition. Shared consensus regarding the importance of natoni and participatory village leadership emerged as key factors supporting cultural preservation. The study implies that the successful preservation of local culture requires sustained collaboration among government institutions, traditional authorities, and community members to strengthen cultural transmission to future generations.